Telomere Length but Not Mitochondrial DNA Copy Number Is Altered in Both Young and Old COPD - Casas-Recasens, Sandra; Mendoza, Nuria; López-Giraldo, Alejandra; Garcia, Tamara; Cosio, Borja G.; Pascual-Guardia, Sergi; Acosta-Castro, Ady; Borras-Santos, Alicia; Gea, Joaquim; Garrabou, Gloria; Agusti, Alvar; Faner, Rosa (Frontiers in Medicine, 2021)
Accelerated ageing has been implicated in the pathogenesis of respiratory diseases as Chronic Obstructive Pulmonary Disease (COPD), but recent evidence indicates that COPD can have roots early in life. Here we hypothesize that accelerated ageing markers might have a role in the pathobiology of young COPD. The objective of this study was to compare two hallmarks of ageing, telomere length (TL) and mitochondrial DNA copy number (mtDNA-CN, as a surrogate marker of mitochondrial dysfunction) in young (≤50 yrs.) and old (>50 yrs.) smokers, with and without COPD. Both, TL and mtDNA-CN were measured in whole blood DNA by qPCR in: 1) young ever smokers with (n=81) or without (n=166) COPD; and 2) old ever smokers with (n=159) or without (n=29) COPD. Multivariable linear regression was used to assess the association of TL and mtDNA-CN with lung function. We observed that in the entire study population, TL and mtDNA-CN decreased with age, and the former but not the latter related to FEV1/FVC (%), FEV1 (% ref.) and DLCO (% ref.). Short telomeres were found both in young and old patients with severe COPD (FEV1 < 50 % ref). We also found that TL and mtDNA-CN were significantly correlated, but their relationship was positive in younger while negative in older COPD patients, suggesting a mitochondrial dysfunction. We conclude that TL, but not mtDNA-CN, is associated with lung function impairment. Both young and old patients with severe COPD have evidence of accelerated ageing (shorter TL), but differ in the direction of the correlation between TL and mtDNA-CN in relation to age.